The photon interactions and build-up factor for gadolinium sodium borate glass: Theoretical and experimental approaches. (November 2021) - Yonphan, S.; Limkitjaroenporn, P.; Borisut, P.; Kothan, S.; Wongdamnern, N.; Alhuthali, Abdullah M.S.; Sayyed, M.I.; Kaewkhao, J.
Abstract: Gadolinium sodium borate glass in compositions of xGd2 O3 : 20Na2 O:(80-x)B2 O3 (where x is 0, 5, 10, 15, and 20 mol%) were prepared by melt quenching technique. The glass samples have been investigated for the physical properties and radiation shielding properties. The glass density and molar volume tended to increase with increasing Gd2 O3 concentration. The theoretical values of radiation shielding were computed by WinXCom program in the energy range 0.015 MeV–15 MeV. The experimental values have been measured in energy range 0.223 MeV–0.662 MeV using Compton scattering technique for variation the energy from Cs-137 source. The experimental values are in good agreement with the theoretical values. From the results, the replacement of B2 O3 by Gd2 O3 helped to increase the mass attenuation coefficients (μm ), effective atomic number (Zeff ) and effective electron density (Neff ). The energy absorption buildup factor coefficients (EABF) and the exposure buildup factor values (EBF) were decreased with the increasing of Gd2 O3 at energy below 2 MeV and show the increase with Gd2 O3 content at energy higher than 2 MeV. The half value layer (HVL) were decreased with increasing of Gd2 O3 . All studied glasses were found to be lower HVL values, when compared with the some standard shielding materials. These results reflected to the ability of gadolinium sodium borate glass for radiation shielding material. Highlights: New shielding glasses from Gd2 O3 based have were developed. The theoretical values of shielding parameters were calculated. The experimental values were measured in energy range 0.223 MeV–0.662 MeV. Shielding properties show better than some standard shielding materials. The Gadolinium Sodium Borate glass is suitable for radiation shielding material.